Effect of Modified Molasses Carbon Filler on Mechanical Properties of Natural Rubber Vulcanizates - Moryadee, Papatsara; Tuamkeaw, Supaporn; Saowapark*, Thanunya (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
In this research, a possibility study was carried out on the utilization molasses, inexpensive by-product of the refining of sugarcane into sugar, as alternative filler in rubber. Liquid molasses was converted to powder form under the heating process. Molasses carbon powder (MCP) was finally obtained. As a result of percentage of carbon content in MCP, it was evident that MCP containing 64.5 percent of carbon. Interestingly, the MCP was rich in carbon as well as carbon black (CB) reinforcing filler in rubber. In order to enhance the mechanical properties of MCP filled NR vulcanizates, MCP was modified with a silane coupling agent such asbis (3-triethoxysilylpropyl) tetrasulfide or Si69. Thus, the present work aims to investigate the role of silane coupling agent on properties of NR vulcanizates filled with MCP. Modified and unmodified MCP was incorporated into the NR with loadings of 30 phr (parts per hundred of rubber) and also compared with CB. All of NR filled with carbon fillers were examined in the term of cure characteristics, tensile properties, tear strength and swelling resistance. From the results, it was observed that the cure times were decreased with the incorporation of silane modified MCP. In addition, torque difference, tensile strength, tear strength and swelling resistance of NR vulcanizates were improved. Keywords: natural rubber, molasses, carbon black, silane coupling agent, filler *Corresponding author: E-mail: bbiirrddtt@hotmail.com, thanunya@webmail.npru.ac.th